2019
DOI: 10.1111/ced.14089
|View full text |Cite
|
Sign up to set email alerts
|

Axillary web syndrome induced by physical exertion

Abstract: Click https://www.wileyhealthlearning.com/ced.aspx for the corresponding questions to this CME article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…2 In recent years, AWS cases unrelated to surgery have started to attract attention. 3,4 Moreover, a couple of cases of idiopathic AWS have also been reported in the literature, to the best of our knowledge, the case described here is the third. 5,6 Here, we present the case of a patient diagnosed with idiopathic AWS and treated with physical ther-apy (PT) with good outcomes.…”
Section: Olgu Sunumumentioning
confidence: 57%
“…2 In recent years, AWS cases unrelated to surgery have started to attract attention. 3,4 Moreover, a couple of cases of idiopathic AWS have also been reported in the literature, to the best of our knowledge, the case described here is the third. 5,6 Here, we present the case of a patient diagnosed with idiopathic AWS and treated with physical ther-apy (PT) with good outcomes.…”
Section: Olgu Sunumumentioning
confidence: 57%
“…In this study, we found an association between vigorous PA performance and risk of developing AWS. The authors who previously examined risk factors for developing AWS found no relationship between training level and increased risk of AWS 47 , 48 , with the exception of a case report that described AWS development after physical effort 49 . Moreover, among the risk factors for the development of AWS should be considered younger age, greater time elapsed since surgery and number of resected lymph nodes 50 , but PA was not considered.…”
Section: Discussionmentioning
confidence: 98%
“…The first study showed that AWS appeared after intense physical activity in a young male squash player and another report presented the development of AWS in an old female after home physical exercises. 9 , 10 Several risk factors are related to AWS, including ethnicity, BMI, extent of surgery, cancer management and axillary metastasis. 2 The incidence of AWS in individuals from African American backgrounds is higher than that in Caucasians and is higher in aggressive surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are only two reports of idiopathic AWS 7 , 8 and two other reports of AWS following physical exertion. 9 , 10 In this case report, an atypical presentation of AWS was demonstrated to draw attention and to increase the awareness of clinicians that this condition (AWS) can develop in healthy subjects without any surgical interference.…”
Section: Introductionmentioning
confidence: 87%